Quasi-stationary states of electrons interacting with strong electromagnetic field in two-barrier resonance tunnel nano-structure - Tkach, M.V.; Seti, Ju.O.; Voitsekhivska, O.M. (Condensed Matter Physics, 2012)
An exact solution of non-stationary Schrodinger equation is obtained for a one-dimensional movement of electrons in an electromagnetic field with arbitrary intensity and frequency. Using it, the permeability coefficient is calculated for a two-barrier resonance tunnel nano-structure placed into a high-frequency electromagnetic field. It is shown that a nano-structure contains quasi-stationary states the spectrum of which consists of the main and satellite energies. The properties of resonance and non-resonance channels of permeability are displayed. Знайдено точний розв’язок нестацiонарного рiвняння Шредiнґера для одновимiрного руху електронiв у електромагнiтному полi довiльних величин напруженостi та частоти. На цiй основi виконано розрахунок коефiцiєнта електронної прозоростi двобар’єрної резонансно-тунельної наноструктури у високочастотному електромагнiтному полi. Показано, що дослiджувана система має квазiстацiонарнi стани, спектр яких мiстить основнi та сателiтнi енергiї. Виявлено властивостi резонансних i нерезонансних каналiв прозоростi двобар’єрної наносистеми.